The Atomic Views of Flat Supply Chains in China - Sekhar Chattopadhyay (International Journal of Engineering Business Management, 2010)
China's domestic supply chain networks are getting flat and unbalanced despite its spectacular growth and rise to the enviable position in the global supply chain arena in recent times. The aftermath of continued investment explosion, especially in the coastal areas of the mainland, calls for an interwoven relationship of Chinese companies with the rest of the global supply chains. However, with new information and communication technologies, the real-time problems arising from this flattened supply chains are much more complex, multifaceted and multidimensional. China needs to re-think and re-focus on better alignment to the western values and cultures while managing its global business activities. This paper discusses four recently developed enterprise models in the light of several case studies conducted recently in Australia, China and India to characterise these new flat supply chains: People-Centric, Molecular Organization, Globally Dispersed and Disaggregated Value Chain. These, apparently different but inherently similar models have a vibrant architecture and system behaviour in their core and propose an alternative approach to address challenges of unbalanced domestic flat supply chains in China and helps the Chinese manufacturers to explore an approach to embrace Western values and cultures by enlarging their sphere of influence.